Apports de l’iconographie sidérale aux problématiques spatiales vidéoludiques : le cas des jeux vidéo horrifiques - Guillaume Baychelier (ReS Futurae)
Science-fiction and the imaginary of cosmos bring a fertile framework to video games. Apart the depth of the fictional worlds that it allows to develop, Space void as a narrative and iconographic trope opens a wide variety of issues linked to the relation between players and the spatiality of video games. Contrasting with the need for guidance that underpins the experience of 3D video games, Space void forms a field that offers no landmarks. As the absolute uncharted territory, Space is dedicated to the rough experience of wandering but also to the pleasure of exploration (No Man’s Sky, 2016). Because of its inherent hostility, Space could be a powerful tool designed to arouse emotions in horror video games. From Dead Space (2008) to Alien : Isolation (2014), fear of void is used in a dialectic that articulates enclosure in cells and effusion of the infinite darkness of Space. In this way, survival horror genre consolidates its game mechanics : being immerged in Space becomes a trial that makes vulnerable to claustrophobic narrowing and also to vertiginous endlessness. Using science-fiction tropes allows to extend the video game space representational modalities but also the content of its experience. This text interrogates the issues of the tensions resulting from the descent into Space void, from an iconological and a gaming perspective.